PENGARUH APLIKASI SISTEM PERANCAH NON FREEZE-DRYING CHA-GELATIN SHEET PADA PROLIFERASI DAN EKSPRESI GEN DIFERENSIASI OSTEOGENIK Runx2, Osterix DAN Osteocalcin SEL PUNCA MESENKIM DARI TALI PUSAT BAYI - , Fransiscus F. A. Kerans, dr. E. Henny Herningtyas, M.Si, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bone has a limited ability to perform self-repair and tissue regeneration, thus becoming the world's health problems. Bone tissue engineering is found to be great solution of bone regeneration therapy. The three basic elements in bone tissue engineering are (1) progenitor cells, (2) extracellular matrix scaffold system as required for the initial proliferation, migration and differentiation of cells, and (3) growth factors. Carbonate Apatite (CHA)-gelatin sheet, as a scaffold system for bone tissue engineering, has been developed by Tissue Engineering team in Faculty of Dentistry, University of Gadjah Mada. The mesenchymal stem cells also known as progenitor cells that have osteoblast-lineage potential. Therefore, in order to design a bone implant that can be tolerated human body, it is need to be tested the effect of the application system based on a synthetic scaffold CHA-gelatin sheet on the ability of proliferation and osteogenic differentiation of mesenchymal stem cells. In this study, mesenchymal stem cells obtained from human umbilical cord because it is one of the richest source of mesenchymal stem cells, and can be isolated easily and non-invasive by explant method. CHA-gelatin sheet was fabricated with two variations of the concentration (solid dissolved in liquid), which are 10 % w/v (CHA/gel-10) and 5% w/v (CHA/gel-05). Each variant uses 25% CHA and 75 % gelatin ratio. Proliferation test performed using the MTT method to determine the ability of proliferation induced by CHA-gelatin scaffold sheet on mesenchymal stem cells. Furthermore, semi-quantitative analysis of gene expression of osteogenic markers Runx2 , Osterix and Osteocalcin using RT-PCR was performed to determine the ability of osteogenic differentiation induction system CHA-gelatin scaffold sheet on mesenchymal stem cells . The results of this study indicate CHA/gel-05 scaffold capable of inducing proliferation of mesenchymal stem cells during 7 days of observation time. Then on osteogenic differentiation observation, scaffolding CHA/gel-10 able to increase the expression of Osterix and Osteocalcin genes of mesenchymal stem cells on day 10 of incubation time. Thus CHA-gelatin sheet scaffold are known to have the ability to induce proliferation and increase osteogenic differentiation of mesenchymal stem cells from human umbilical cord . However, it still needs further in-vivo testing